A Brief Review on Chemical Constituents of Some Medicinally Important Species of the Genus Plumeria - M. Hasan, Aidroos; Joshi, B.C.; Dobhal, M.P.; Sharma, M.C. (Asian Journal of Chemistry, 2010)
The present communication deals with a brief review of some species from Plumeria (family—Apocynaceae) which are used in the treatment of various ailments like bitter tonic, expectorant, purgative skin diseases, diuretic, antipsychotic, antitumor agents and as inhibitors of human immuno-deficency virus type-1 (HIV-1).